Getting students to 'do' introductory sociology: Analysis of a blended and flipped interactive workshop model. (September 2021) - Baker, Sarah; Buttigieg, Bob; Cantillon, Zelmarie; Pavlidis, Adele; Rodriguez Castro, Laura; Watson, Ash
Blended learning and flipped classroom models are increasingly encouraged in higher education, where notions of flexibility and technological development inform institutional systems and strategies. This article presents results from an Australian study on redesigning and delivering an introductory sociology course using a combination of such models. Four central elements of the redesign are highlighted: overall course format; use of mini-lectures; face-to-face activities; and our assessment model. We present analysis of students' and instructors' understandings and experiences of the redesign over three course iterations to offer insight into the unfolding and responsive dynamics involved in implementing blended and flipped models. We aim to contribute to the ongoing implementation of similar models in the context of changing institutional environments and expectations, as well as to broader projects for pedagogical enrichment in sociology.